Thermal Barrier Coatings—A State of the Art Review - Thakare, Jayant Gopal; Pandey, Chandan; Mahapatra, M. M.; Mulik, R. S. (Metals and materials international, 2021)
Thermal barrier coatings (TBCs) have seen considerable advancement since the initial testing and development of thermal spray coating. Thermal barrier coatings are currently been utilized in various engineering areas which include internal combustion engines, gas turbine blades of jet engines, pyrochemical reprocessing units and many more. The development of new materials, deposition techniques is targeted at improving the life of the underlying substrate. Hence, the performance of the coating plays a vital role in improving the life of substrate. The scope for advancement in thermal barrier coatings is very high and continuous efforts are being made to produce improved and durable coatings. Thermal barrier coatings have the potential to address long term and short-term problems in gas turbine, internal combustion and power generation industry. The study of thermal barrier coating material, performance and life estimation is a critical factor that should be understood to introduce any advancement. The present review gives an overview of the thermal spraying techniques and current advancements in materials, mechanical properties, understanding the high temperature performance, residual stress in the coating, understanding the failure mechanisms and life prediction models for coatings. Graphic Abstract